Ilmu Pendidikan Islam Versi Perspektif Nasional dan Lembaga Pendidikan - Munir Munir (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2017)
Education is an elementary element that can not be separated from the theological aspect. Theological Islamic commitment to education can be traced to the Qur'an of al-Alaq (96): 1-14. The verses in this letter describe the significance of true knowledge that must be known and spread by Muslims in particular and mankind in general. Abdullah Yusuf Ali explains that the phrase "teaching" and "recitation" in the verses implies that the government of teaching and reading (researching and so on) is not limited to the delivery of the message of God to be done by the Apostle, but also universal, on the task of spreading the truth by all who read and understand the teachings of the Qur'an.